Inflammatory diseases of the non-lactating female breasts. (January 2015) - Gopalakrishnan Nair, C.; Hiran,; Jacob, Pradeep; Menon, Riju R.; Misha,
Abstract: Chronic inflammatory diseases of the non-lactating breasts cause considerable difficulty in diagnosis and treatment. There is a spectrum of aetiological factors ranging from infection to autoimmune disorders. The disease causes considerable morbidity and psychological distress in relatively young females. The study aimed to analyse the spectrum of chronic disease and to formulate a treatment protocol.Method : Female patients with histological confirmation of inflammatory disease of the breast in the non-lactational phase were included in the study. The patients were categorized based on histological findings supplemented with immunohistochemical staining with CD3 and CD20 antibodies.Result : Out of 50 patients included in the study, 38 patients (76%) were diagnosed as idiopathic granulomatous mastitis (IGM) and 12 (24%) patients as periductal mastitis (PD). The possible aetiology of IGM was localized autoimmunity as evidenced by the infiltration of CD3 positive T lymphocyte. Systemic prednisolone was given for 6 months and 95.6% patients were disease-free after 24months. Out of 15 patients who did not receive prednisolone, only 2 patients were disease-free after 24 months ( p = .003).Conclusion : Idiopathic granulomatous mastitis is an uncommon inflammatory disease of the non-lactating breast. The combination of limited surgical treatment and systemic prednisolone given for 6 months effectively controls the disease as well as prevents recurrence. Highlights: The aetiology of Idiopathic Granulomatous Mastitis is uncertain. But our study noted CD 3 positive lymphocyte infiltration of the lesion. Aerobic and anaerobic culture did not did not grow bacteria in 86.8% patients with Idiopathic Granulomatous Mastitis. Special stains to identify presence of Mycobacterium species and Fungus were non-contributory. Limited operative procedure and systemic prednisolone were effective in preventing recurrence.